AB0288 Rheumatoid Arthritis Impact Disease (RAID) among Moroccan Patients. (10th June 2014) - El Kabbaj, S.; Allali, F.; Medrare, L.; Benslama, I.; Lakhdar, T.; Ngeuleu, A.; Rkain, H.; Hajjaj Hassouni, N.
Abstract : Objectives: Score distributions and associations between the RAID score and RA demographic and disease related variables were examined in rheumatoid arthritis (RA) patients. Methods: 103 patients diagnosed were enrolled in the study. Disease activity was assessed through the Disease Activity Score (DAS) 28 scale. quality of life was evaluated with The EQ-5D, and Health Assessment Questionnaire (HAQ) was completed by all patients. Pain and fatigue were evaluated with pain Visual analogic scale (VAS) and fatigue VAS respectively. The Rheumatoid Arthritis Impact disease (RAID) was used for the evaluation of the impact of rheumatoid arthritis. Results: The mean RAID was 3, 78±2, 15. The distribution of the RAID: 32% had a score between 0 and 2, and 13.5% between 7 and 10. In univariate analysis the RAID score correlated with pain (r=0, 79; IC95% (0, 05-0, 06); p<0, 001), fatigue (r=0, 80; IC95% (2, 2-3, 7); p<0, 001), morning stiffness (r=0.53; IC95% (0, 017-0, 03); p<0.001), DAS28 (r=0.75; IC95% (0, 7-1); p<0.001), HAQ (r=0, 75; IC95% (1, 7-2, 4); p<0, 001), EQ-5D (r= -0, 72; IC95% (-4, 7_-3, 2) p<0.001). After multivariate analysis the pain (r=0, 15; IC95% (0, 01-0, 35); p<0, 001), fatigue (r=0, 18; IC95% (0, 17-1, 2); p<0, 01), DAS28 (r=0, 26; IC95% (0, 2-0, 3); p<0, 001), HAQ (r=0, 2; IC95% (0, 18-0, 9); p<0, 01) and EQ-5D (r= -0, 26; IC95% (-1, 9_-0, 4); p=0, 001) still strongly associated with RAID. Conclusions: This study suggested that RAID associated with disease activity, functional capacity, Pain, fatigue and EQ-5D. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4863